2012
DOI: 10.1517/14656566.2012.657177
|View full text |Cite
|
Sign up to set email alerts
|

Drugs and mitochondrial diseases: 40 queries and answers

Abstract: Randomized clinical trials are necessary to establish efficacy and safety of drugs. Multicenter collaboration is essential for the advancement of therapy for mitochondrial disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 132 publications
0
53
0
Order By: Relevance
“…As reported, VPA hepatotoxicity includes microvesicular steatosis, steatohepatitis, fibrosis, hepatocellular carcinomas, and even fulminant hepatitis, 46-48 mainly due to mitochondrial toxicity shown both in rodents and humans. 50,51 In this study, we have demonstrated that NaB protects HepG2 cells and primary rat hepatocytes from VPA-induced toxicity, by reducing cellular and mitochondrial oxidative damage. 50,51 In this study, we have demonstrated that NaB protects HepG2 cells and primary rat hepatocytes from VPA-induced toxicity, by reducing cellular and mitochondrial oxidative damage.…”
Section: Discussionmentioning
confidence: 74%
“…As reported, VPA hepatotoxicity includes microvesicular steatosis, steatohepatitis, fibrosis, hepatocellular carcinomas, and even fulminant hepatitis, 46-48 mainly due to mitochondrial toxicity shown both in rodents and humans. 50,51 In this study, we have demonstrated that NaB protects HepG2 cells and primary rat hepatocytes from VPA-induced toxicity, by reducing cellular and mitochondrial oxidative damage. 50,51 In this study, we have demonstrated that NaB protects HepG2 cells and primary rat hepatocytes from VPA-induced toxicity, by reducing cellular and mitochondrial oxidative damage.…”
Section: Discussionmentioning
confidence: 74%
“…However, idebenone may represent an inhibitor of both the redox and proton-pumping activity of complex I [5] and may cause mitochondrial depolarization and reduced nicotinamide adenine dinucleotide (NADH) depletion [4, 6]. Most recently, idebenone has been shown to be effective in improving recovery after the onset of vision loss in Leber’s hereditary optic neuropathy (LHON).…”
Section: Augmentation Of Respiratory Chain Componentsmentioning
confidence: 99%
“…Most therapeutic strategies to treat this condition use supplements and enzyme cofactors to enhance mitochondrial metabolism and activity of the respiratory chain [34] . The treatment of choice may be represented by the combination of L-arginine (usually applied intravenously at a dosage of 0.4–0.5 g/kg in the acute phase and then switched to long-term oral supplementation) [33] , [35] , carnitine and coenzyme Q10, plus corticosteroids for the vasogenic oedema and anti-epileptic drugs or other supportive treatments when needed [36] . Other molecules such as creatine and idebenone have been suggested to decrease lactic acid levels and reduce stroke-like episodes [37] , [38] .…”
Section: Monogenic Diseasesmentioning
confidence: 99%